The effectiveness of EM4 addition in the biofilter to reduce oil andfat content in the restaurant liquid waste - Firnandito, Anggi Ade; Harahap, Sampe; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractRestaurant liquid waste may pollute aquatic environment as it has high oil and fat content. It should be processed before being flown to environment. This study aims to understand the effectiveness of EM4 addition in reducing oil or fat content in the restaurant liquid waste. This research was carried out in February 2020 at the Naga Sakti street No. 18, Al Ma’ruf alley, Pekanbaru. A Completely Randomized Design (CRD) was applied with 3 treatments, namely P0 (without EM4), P1 (7.5 ml EM4), P2 (10 ml EM4), P3 (12.5 ml EM4) and 3 replications. The restaurant liquid waste was kept in the biofilter tank for 6 days (3 days in the anaerob and 3 days in the aerob tanks) and then oil and fat were analyzed. The best result was obtained in the P1 (7.5 ml EM4). In that treatment oil and fat decreased from 16.20 mg/L into 2.67 mg/L. The treated liquid waste was then use for rearing Pangasius sp. sized 4-5 cm for 96 hours. The survival rate of the fish was 100%. Data obtained shown that the addition of EM4 to the biofilter tanks was able to reduce the fat content in the restaurant liquid waste.Keywords :Effective Microorganism-4, Anaerob tanks, Aerob tanks, Pangasius sp.